Diagnosis and analysis of unexplained cases of childhood encephalitis in Australia using metatranscriptomic sequencing. (29th April 2022) - Li, Ci-Xiu; Burrell, Rebecca; Dale, Russell C.; Kesson, Alison; Blyth, Christopher C.; Clark, Julia E.; Crawford, Nigel; Jones, Cheryl A.; Britton, Philip N.; Holmes, Edward C.
Abstract : Encephalitis is most often caused by a variety of infectious agents identified through diagnostic tests utilizing cerebrospinal fluid. We investigated the clinical characteristics and potential aetiological agents of unexplained encephalitis through metagenomic sequencing of residual clinical samples from multiple tissue types and independent clinical review. Forty-three specimens were collected from 18 encephalitis cases with no cause identified by the Australian Childhood Encephalitis study. Samples were subjected to total RNA sequencing ('metatranscriptomics') to determine the presence and abundance of potential pathogens, and to describe the possible aetiologies of unexplained encephalitis. Using this protocol, we identified five RNA and two DNA viruses associated with human infection from both non-sterile and sterile sites, which were confirmed by PCR. These comprised two human rhinoviruses, two human seasonal coronaviruses, two polyomaviruses and one picobirnavirus. Human rhinovirus and seasonal coronaviruses may be responsible for five of the encephalitis cases. Immune-mediated encephalitis was considered likely in six cases and metatranscriptomics did not identify a possible pathogen in these cases. The aetiology remained unknown in nine cases. Our study emphasizes the importance of respiratory viruses in the aetiology of unexplained child encephalitis and suggests that non-central-nervous-system sampling in encephalitis clinical guidelines and protocols could improve the diagnostic yield.